Digestible trypthophan and digestilbe lysine ratios in diets for growing japanese quails - Lima, Heder José D'Ávila; Barreto, Sergio Luiz Toledo; martinez, juliana freitas (Research, Society and Development, 2020)
The objective of this study was to evaluate the effects of different tryptophan and digestible lysine ratios for growing Japanese quails (1 to 40 days of age) with repercussions on the early stage of production (41 to 110 days of age). A total of 1000 one day old Japanese quails were distributed at random, with five tryptophan and digestible lysine ratios, 10 replicates and 20 birds per experimental unit. A tryptophan- deficient basal diet was formulated with 1.48 g of digestible tryptophan /kg, corresponding to a ratio of tryptophan and lysine of 0.14. This basal diet was supplemented with five levels of L-tryptophan (98%), replacing glutamic acid corresponding to the tryptophan and lysine ratio of 0.14 (no supplementation); ratios of 0.16; 0.18; 0.20 and 0.22, being the diets isocaloric and isonitrogenous. The performance of the birds in the growing and egg laying phases was evaluated. Although body weight and weight gain until 40 days of age had increased (P